Adequacy of senior registrar training in accident and emergency medicine over the last 5 years. Issue 3 (September 1988) - Driscoll, P; Cope, A; Miles, S A
Abstract : This study investigated the limitations of the present Senior Registrar training programmes in A&E Medicine. A completed questionnaire was returned from 46 of the 48 Consultants who had taken up post in the last 5 years and had themselves studied on one of the established training programmes. The positive views of the clinical training contrast sharply with the administrative and managerial components. Around 80% of the new Consultants had no training in clinical budgeting or ordering equipment and only half had experience of appointing staff and organizing locums. This is worrying as over 63% had or are currently facing staffing problems and 69% have financial or equipment difficulties. A more active training programme in A&E administration and management is recommended.